2019
DOI: 10.1002/med.21581
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design opportunities presented by solvent‐exposed regions of target proteins

Abstract: Solvent‐exposed regions, or solvent‐filled pockets, within or adjacent to the ligand‐binding sites of drug‐target proteins provide opportunities for substantial modifications of existing small‐molecular drug molecules without serious loss of activity. In this review, we present recent selected examples of exploitation of solvent‐exposed regions of proteins in drug design and development from the recent medicinal‐chemistry literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 202 publications
(371 reference statements)
0
24
0
Order By: Relevance
“…Prodrug strategy is an effective approach in the improvement of druggability 105 . Commonly, a prodrug contains the parent drug with a spacer and a specifier.…”
Section: Improvement Of Pk Profilesmentioning
confidence: 99%
“…Prodrug strategy is an effective approach in the improvement of druggability 105 . Commonly, a prodrug contains the parent drug with a spacer and a specifier.…”
Section: Improvement Of Pk Profilesmentioning
confidence: 99%
“…The molecular details of the binding mode between the 3 / 4 and RT indicated that the two protein–solvent interfaces (i.e., the tolerant region I and the entrance channel) provide an underexploited region for the development of novel NNRTIs. In addition, both of them can favorably accommodate various substituents and be involved in the formation of multiple molecule–protein interactions, thus becoming valuable sites for further exploration. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, both of them can favorably accommodate various substituents and be involved in the formation of multiple molecule−protein interactions, thus becoming valuable sites for further exploration. 25,26 In the present work, based on the above detailed analysis, a series of novel dihydrothiopyrano [4,3-d]pyrimidine derivatives featuring the piperidin-4-yl-amino moiety or p-cyanoaniline analogues in the right wing were rationally designed via the scaffold hopping and molecular hybridization strategies (Figure 2). Nowadays, the concept of "fraction of sp 3 carbon atoms" (i.e., Fsp 3 , the ratio of the number of carbon atoms with sp 3 hybridization to the total number of carbon atoms) has been proposed to determine the carbon saturation of molecules and characterize the complexity of molecular space structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1b) indicated that the right benzonitrile moiety pointed to a rather plastic "groove" of NNIBP, known as the solvent-exposed tolerant region I [29]. Solvent-exposed regions could well accommodate diverse polar or hydrophilic substituents, which contribute to establish additional and specific protein-ligand interactions, as well as to elevate physicochemical properties [30]. Thus, the strategy of exploiting solvent-exposed regions has great potential in improving binding affinity, enhancing selectivity and overcoming drug resistance.…”
Section: Introductionmentioning
confidence: 99%